2003
DOI: 10.3998/ark.5550190.0004.113
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic characterization and in vitro antitumor activity of new trans 1-heteroaryl-2-(1-methylpyridinium-2-yl) ethylenes

Abstract: The synthesis and spectroscopic characterization of trans 1-heteroaryl-2-(1-methylpyridinium-2-yl) ethylene iodides is reported. The 5-(4-bromophenyl)furan derivative exhibited the highest in vitro antitumor activity against MCF7 (breast) and LNCap (prostate) carcinoma cells. Solvatochromic and NMR shifts provided evidence for modulation of electronic parameters which could be used to optimize frequency emission and conversion efficiency in such push-pull conjugated systems, which are potential components of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…All the designed structures possess a pyridinium or a quinolinium salt unit (except for the 1 that presents an imidazolium salt), separated through an ethylenic double bond from another unit, heterocyclic or not, variously substituted to explore a large chemical space with different biological behaviours and responses. As rationalized in previous studies [8][9][10][11][12][13][14][15][16] both the presence of four rings and the replacement of the pyridinium ring with a quinolinium one increased the in vitro activity. Starting from this assumption, in order to obtain compounds both active and inactive we designed new molecules by introducing new substituents and a fifth ring into the scaffold (Scheme 1).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…All the designed structures possess a pyridinium or a quinolinium salt unit (except for the 1 that presents an imidazolium salt), separated through an ethylenic double bond from another unit, heterocyclic or not, variously substituted to explore a large chemical space with different biological behaviours and responses. As rationalized in previous studies [8][9][10][11][12][13][14][15][16] both the presence of four rings and the replacement of the pyridinium ring with a quinolinium one increased the in vitro activity. Starting from this assumption, in order to obtain compounds both active and inactive we designed new molecules by introducing new substituents and a fifth ring into the scaffold (Scheme 1).…”
supporting
confidence: 62%
“…The mechanism through which these heterocycles exert antiproliferative and cytotoxic effects remains unclear. Previous work of our group reported the binding of similar heterocyclic compounds with an oligonucleotide [10][11][12][13][14][15][16] and, among these, the compound 6 tested here. The analysis of the molecules using intracellular fluorescence spectroscopy revealed that 5 and 6 emitted, respectively, in the deep red (l ex/em = 633/647 nm) and red (l ex/em = 543/598 nm) wavelength spectral range, which enabled us to follow the localization of the molecules inside the cells.…”
Section: Communication Molecular Biosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ligand-DNA complexation constants obtained were in the range 10 5 -10 6 M −1 , high enough to be of interest for therapeutic applications, in agreement with preliminary results of in vitro tests 35 and those reported elsewhere for analogous compounds. 17,[36][37][38] For compounds 1 and 4 the association constants were derived by both spectrophotometric and fluorimetric titrations. The values of K a and K f thus obtained are not so different (also considering the complexity of the systems and the different approach of the two methods), both of them indicating a strong ligand-DNA interaction.…”
Section: Femtosecond Transient Absorptionmentioning
confidence: 99%